Analisis Faktor-Faktor Yang Mempengaruhi Ketimpangan/Kesenjangan Kemandirian Fiskal Di Provinsi DKI Jakarta Dan Papua Barat - Virnalici Virnalici; Puji Wahono (Management Studies and Entrepreneurship Journal (MSEJ), 2023)
The aim of this reearch is to analyze the variables that influence the inequality/gap in fiscal independence in the Provinces of DKI Jakarta and West Papua, looking at the ability of a region or province in Indonesia to generate its own income and manage regional or provincial finances without relying too much on aid or transfers from central government or other external sources, which in turn may influence the feasibility of investing in that region or province. In this case, when carrying out investment management, investors may consider the level of fiscal independence of a region or province as part of the risk analysis and potential investment returns. The variables used include: original regional income (PAD), balancing funds (DAU, DBH, DAK), transfers to regions and village funds (TKDD), other income which includes grants, emergency funds, adjustment funds and special autonomy (Otsus), financial assistance, Inter-Regional Transfer Income, and other income in accordance with statutory provisions. The data used is secondary data (time series) spanning the 2015 Fiscal Year; 2016;2017; 2018; 2019 and 2020 which were analyzed using the Hunter formula (1977) and descriptive methods and literature studies or often known as literature studies. The results of the analysis show that there is a very large inequality/gap between the fiscal independence of DKI Jakarta and West Papua. Both in terms of population density and regional GDP levels in the provinces of DKI Jakarta and West Papua. This inequality/gap occurs because PAD has a very large positive influence on DKI Jakarta compared to West Papua, so that West Papua uses Balancing Funds, TKDD, and other income to finance its expenditure. Meanwhile, DKI Jakarta only needs to use PAD to finance its regional expenditure. Stable economic conditions and good fiscal policies in DKI Jakarta can also create a more attractive investment environment compared to West Papua Province which has low fiscal independence.